1985
DOI: 10.1111/j.1365-3024.1985.tb00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Giardia muris‐induced depression of the primary immune response in spleen and mesenteric lymph node cell cultures to sheep red blood cells

Abstract: Primary in vitro plaque-forming cell (PFC) responses to sheep red blood cells (SRBC) were examined for spleen and mesenteric lymph node (MLN) cell populations from susceptible (A/J) and resistant (B10.A) mice during the infection with Giardia muris. Spleen and MLN cells isolated from mice during the acute phase of the infection were less responsive to SRBC in vitro than those from uninfected mice. Depressed anti-SRBC PFC response was detected earlier and was more pronounced in MLN cell cultures when compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The number of IgM and IgG plaque-forming cells and the hemagglutination titer of both IgM and IgG decreased during the acute phase of the infection. Interestingly, peritoneal exudate macrophages from infected mice were slightly less cytostatic against tumor cells at the time of the elimination phase (19,31). Belosevic et al (16) reported that spleen and MLN cells isolated from mice during the acute phase of the infection were less responsive to SRBC.…”
Section: Immunosuppression In Infected Micementioning
confidence: 99%
“…The number of IgM and IgG plaque-forming cells and the hemagglutination titer of both IgM and IgG decreased during the acute phase of the infection. Interestingly, peritoneal exudate macrophages from infected mice were slightly less cytostatic against tumor cells at the time of the elimination phase (19,31). Belosevic et al (16) reported that spleen and MLN cells isolated from mice during the acute phase of the infection were less responsive to SRBC.…”
Section: Immunosuppression In Infected Micementioning
confidence: 99%
“…The number of IgM and IgG plaque-forming cells and the hemagglutination titer of both IgM and IgG decreased during the acute phase of the infection. Interestingly, peritoneal exudate macrophages from infected mice were slightly less cytostatic against tumor cells at the time of the elimination phase (19,31). Belosevic et al (16) reported that spleen and MLN cells isolated from mice during the acute phase of the infection were less responsive to SRBC.…”
Section: Immunosuppression In Infected Micementioning
confidence: 99%